Comparing Customer Satisfaction: The Role of User Experience in Online vs Offline Shopping - Sompura, Jayesh; Ramchandani, Paras; Shriyal, Harsh; Raithatha, Bhavya; Chauhan, Rahul; Maseleno, Andino; Isnanto, R. Rizal (Greenation Research & Yayasan Global Resarch National, 2024)
This research explores the influence of demographic factors, specifically age and income, on consumer preferences and behavior regarding online and offline shopping. Using a sample of 114 respondents from Ahmedabad, the study assesses the satisfaction, convenience, and trust associated with both shopping modes. ANOVA analysis reveals that while age and income significantly affect online enhancements and offline convenience, other factors like trust and barriers remain relatively consistent across demographics. The results emphasize the importance of omnichannel strategies, blending the convenience of online shopping with the tactile and trust-based advantages of physical stores. Future research should explore additional demographic and psychological variables, as well as the adoption of advanced technologies like augmented reality (AR) in shopping, to better understand the evolving consumer landscape. The findings offer global insights relevant to both emerging and developed markets.